Non-compliance Analysis of Independent Participants Paying BPJS Health Contributions After Utilization of Delivery Services - Adila Solida; Andy Amir; Dwi Noerjoedianto (Lembaga Pengembangan Kinerja Dosen, 2022)
Losses experienced by BPJS Health due to payment of contributions that have been stopped for participants who have used maternity services of more than 200 billion in a span of 2 years. It was recorded that 64.7% of mothers who were about to give birth registered as participants a month before giving birth and then quit (43%) or did not comply with the payment after delivery. The largest percentage comes from independent participants or non-wage recipients (PBPU). In Jambi Province, non-compliance in paying BPJS Health contributions is the highest in Jambi City. There were 77,489 participants in arrears in 2021 which resulted in a loss of 60.1 billion. Non-compliance in paying dues comes from multiple factors. The purpose of this study is to analyze the factors causing the non-compliance of independent participants in paying BPJS Health contributions after utilizing childbirth services in Jambi City. A quantitative study approach with a cross-sectional design conducted in Jambi City in 2022. There were 96 respondents who were selected based on the accidental sampling technique. The study instrument was a questionnaire. Quantitative data processing through the stages of editing, coding, entry and cleaning with SPSS. Data analysis consisted of univariate analysis and bivariate analysis using chi-square test. The results of the study found that as many as 33.3% of independent participants did not comply in paying BPJS Health contributions after using childbirth services. There is a significant relationship between the number of family members (p = 0.001), knowledge (0.000), perception of illness (p = 0.001), clinical assessment (p = 0.000), and willingness to pay (WTP) with the non-compliance of independent participants in paying BPJS Health contributions. after the use of maternity services. It is recommended for BPJS Health to consider the application of the waiting period method for participants who will take advantage of maternity services. As well as increasing promotive activities for the Jambi City Government in educating and increasing public awareness about the importance of health insurance in protecting household financing.